Sunday

December 21, 2014

December 21, 2014

Posted by **Sara** on Tuesday, March 27, 2007 at 5:08pm.

f(a)=-4, g(a)=c, g(c)=10, f(c)=15

f'(a)=8, g'(a)=b, g'(c)=5, f'(c)=6

If h(x)=f(g(x)). find h'(a)?

i'm not really sure how to get the answer. g'(a)=b, f'(b)=? How do i go about doing this. My reasoning must be wrong.

h'(x)= f'(g(x))*g'(x)

if x=a

h'(a)=f'(g(a))*g'(a)

=f'(c) * b = 6b

check my thinking.

**Answer this Question**

**Related Questions**

calculus - Assume that x and y are differentiable functions of t. Find dy/dt ...

Calculus - Assuming that f and g are functions differentiable at a (though we do...

Calculus - given that f, g, and h are differentiable functions and f(g(h(x))) = ...

calculus - find f' for each of the following where g and k are differentiable ...

calculus - Find f' for each of the following where g and k are differentiable ...

Calculus - Suppose f and g are functions that are differentiable at x = 1 and ...

Calculus - Suppose f and g are functions that are differentiable at x=1 and that...

Calculus - Below is a table containing information about differentiable ...

Math - suppose u and v are functions of x that are differentiable at x=2 and ...

Calculus - A steady wind blows a kite due west. The kite's height above ground ...